Trabajo infantil y la integración social en los niños, niñas y adolescentes del proyecto ETI Loja, en la actualidad - Muñoz Medina, Jessica del Carmen (2025)
Child labor is a social problem that affects millions of children and adolescents around the world. This reality not only limits their access to education, but also has serious consequences on their physical, emotional and social development. The main objective of the research focused on the impact of this problem on the social development of children and adolescents who are part of the ETI Project in Loja. For this purpose, a mixed methodology was used, conducting a semi-structured interview with the technical team of the ETI Project in order to identify the factors that contribute to the persistence of child labor in the city and a Likert Scale questionnaire applied to children and adolescents to learn about the impact of child labor in their daily lives. The results revealed that child labor is closely related to socioeconomic factors, family problems and, in many cases, cultural practices, seriously affecting the development and social integration of children and adolescents, limiting recreational time, quality family time, and affecting their academic performance. The technical team agreed 100% on the seriousness of this situation. As an intervention proposal, the creation of a life project for each child and adolescent was proposed, focused on identifying and strengthening their dreams, skills and aspirations. This approach seeks not only to eradicate child labor, but also to provide them with tools to build a future full of opportunities